Transformation strategies for facilities management in Malaysia / Maszuwita Abdul Wahab - Maszuwita, Abdul Wahab (2016)

(untitled)
The integration within strategic, tactical and operational level is the main aim in the Facilities Management (FM) industry in Malaysia. In achieving this integration, FM trails such as people, business, property and information are very significant. Therefore, a study of transformation strategies in FM for business success is carried out by adopting the Organizational Behaviour (OB) to improve and upgrade the current system for a better performance. The objectives of this study are to identify the essential elements for FM integration, to analyse the critical success factors of OB and FM to achieve optimum level of performance, to analyse closer relationship within people, facility support and facilitation for a collaborative strategy and to develop the transformation strategies for FM in Malaysia. In order to achieve these objectives, Sequential Explanatory Design was applied that comprises the quantitative and qualitative methods. For the quantitative method, questionnaires were distributed to the built environment respondents which the sample size is approximately 341 from the overall population. By using the SPSS software, the quantitative data were analysed. Both measurement model and structural model were developed to foresee the relationship among the variables for the development of the transformation strategies framework. Meanwhile for the qualitative method, a semi structured interview within fifteen (15) FM expertise were carried out to validate the quantitative data and were presented in a tabular form. The purpose of this validation is to support the data by featuring the comments from the expertise for FM continuity. As a conclusion, the OB measures that consist of organizational environment and competitive skills provided insights that affect the FM performance. Aforementioned, the transformation strategies framework were developed in order to act as a knowledge contribution and as a mantra of success for the FM industry in Malaysia to improve the current situation towards FM continuous improvement.